Environmental regulations and labor markets - Olivier Deschenes (IZA World of Labor, 2018)
Environmental regulations such as air quality standards can lead to notable improvements in ambient air quality and to related health benefits. But they impose additional production costs on firms and may reduce productivity, earnings, and employment, especially in sectors exposed to trade and intensive in labor and energy. Growing empirical evidence suggests that the benefits are likely to outweigh the costs.
Keywords: J23; Q52; Q54; Q48; Q58; 330; job displacement; employment; productivity; air quality standards; regulation